2014
DOI: 10.5935/1678-9741.20140066
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone protects end organs from abdominal aorta ischemia/ reperfusion injury in a rat model

Abstract: IntroductionPrevious studies have demonstrated that thymoquinone has protective effects against ischemia reperfusion injury to various organs like lungs, kidneys and liver in different experimental models.ObjectiveWe aimed to determine whether thymoquinone has favorable effects on lung, renal, heart tissues and oxidative stress in abdominal aorta ischemia-reperfusion injury.MethodsThirty rats were divided into three groups as sham (n=10), control (n=10) and thymoquinone (TQ) treatment group (n=10). Control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…In the present study, we have observed that TQ could protect the liver from OLZ-induced liver injury. We measured TAS, TOS, and OSI levels at the same time to evaluate the oxidative stress status more accurately, and found that serum TAS levels increased and TOS/OSI levels prominently decreased with TQ treatment as in the previous studies (44). Likewise, OLZ administration resulted in a decrease in the liver TAS level and have also reported a decline in TAS after OLZ exposure (43).…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, we have observed that TQ could protect the liver from OLZ-induced liver injury. We measured TAS, TOS, and OSI levels at the same time to evaluate the oxidative stress status more accurately, and found that serum TAS levels increased and TOS/OSI levels prominently decreased with TQ treatment as in the previous studies (44). Likewise, OLZ administration resulted in a decrease in the liver TAS level and have also reported a decline in TAS after OLZ exposure (43).…”
Section: Discussionmentioning
confidence: 80%
“…Antioxidant supplementations of Thymoquinone in Nigella sativa extract is beneficial in increasing natural antioxidants of the body, so that the expression of oxidative stress can be suppressed and skeletal healing process can be held without hindrance. [22][23][24] Continual data which were used as parameters of study is osteoblast amount, calculated from pathology anatomical samples and observed with microscope. Number of osteoblasts in rat samples with fracturing process of tibial bones exhibit more abundant number of cells in groups with administration of Nigella sativa extract compared to the amount of cells in control groups (groups with Thymoquinone administration =16.625±3.074 , control groups =4.688±2.024).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies about osteoporosis also supports the opinion of increasing ROS resulting in bone structural destruction, which is caused by the increase of osteoclast activities and disturbance to osteoblasts' functions, which in turn, reduce the number of osteoblasts from collagen synthesis. 17,20,24…”
Section: Discussionmentioning
confidence: 99%
“…The serum MDA and NO levels significantly decreased in both cases compared with the active controls (25). Intraperitoneally administered thymoquinone, which is an active component of NS, was found to be efficient in decreasing the oxidative stress in an aorta ischemia and reperfusion model (26). Hosseinzadeh et al (6) reported that thymoquinone and NS had inhibitory effects against the lipid peroxidation process in cerebral ischemia and reperfusion injury in rats.…”
Section: CDmentioning
confidence: 99%